A high statistics lattice calculation of heavy-light meson decay constants - Chris Allton (Physics Letters B, 1997)
We present a high statistics study of the D- and B-meson decay constants. The results were obtained by using the Clover and Wilson lattice actions at two different values of the lattice spacing $a$, corresponding to $β=6.0$ and 6.2. After a careful analysis of the systematic errors present in the extraction of the physical results, by assuming quite conservative discretization errors, we find $f_{D_s}=237 ± 16$ MeV, $f_{D} = 221 ± 17$ MeV ($f_{D_s}/f_D=1.07(4)$), $f_{B_s} = 205 ± 35$ MeV, $f_{B} = 180 ± 32$ MeV ($f_{B_s}/f_B=1.14(8)$), in good agreement with previous estimates.